A study of policy processes and implementation of Malaysia's telehealth initiative / Nuraidah Mohd Marzuki - Nuraidah, Mohd Marzuki (2018)
In 1997, Malaysia introduced Telehealth as part of the Multimedia Super Corridor (MSC) programme (Telehealth-MSC). The aspiration to transform the national healthcare from illness-focused to wellness-focused by the year 2020 was laid out in the ‘Telemedicine Blueprint’. However, implementation progress remains below expectations. In 2012, only about 10% of the government healthcare facilities had some form of Telehealth system in place. This suggests an ‘implementation gap’, as the policy statements for Malaysia’s Telehealth remains unrealised. Literature suggests that implementing large scale Telehealth requires proper planning, supported by well-defined policies, rules and standards across healthcare levels. A deeper understanding for the Telehealth ‘implementation gap’ provides explanations to be acted upon and renewed inputs for modified strategies for Telehealth policies in Malaysia. To understand the problems of national Telehealth policy, this thesis examined the policy formulation and the policy implementation from 1995 to 2012. The analysis was guided by a conceptual framework comprised a two-part policy analysis – Kingdon’s Multiple Stream Theory for the policy formulation stage and Normalisation Process Theory for the policy implementation stage. The analysis suggested that, since 1985 the Ministry of Health (MoH) began to computerise its hospitals and clinics and had plans to create an integrated electronic network across the country. It was to modernise healthcare delivery and improve health information management to overcome the challenges of increasing healthcare demands with limited resources. When Prime Minister Mahathir introduced MSC in 1995, the Director-General of Health (DG) played an important role as the policy entrepreneur during the policy formulation and setting the agenda for iv Telehealth. It was seen legitimate and feasible under the MoH plans, and federal government was prepared to allocate funding and provide various forms of incentives. The DG and his policy community continued to support evidence to implement Telehealth with the introduction of the ‘Telemedicine Blueprint’ congruent with the reform intention of the national political leader. Implementation was top-down and the federal government appointed two consortia to complete the Telehealth pilot by 2005. It started with four Telehealth components: Lifetime Health Plan (LHP), Teleconsultation (TC), Mass Customised Personalised Health Information and Education (MCPHIE) and Continuing Medical Education (CME). However, there were obstacles encountered along the ‘downstream’ policy implementation processes. Four issues of policy implementation were identified: (1) lack of coherence or inconsistent decision-making among MoH’s top-level management officials on Telehealth policy priority; (2) difficulties to maintain collective action among the multi-agency partnerships during the system development phase; (3) limited cognitive participation or lack of Telehealth adoption among MoH personnel; and (4) limited capacity to conduct evaluation studies to measure Telehealth outcome or effectiveness (reflexive monitoring). This thesis findings have shown complex socio-technical features of Telehealth policy against a backdrop of the wider political and economic uncertainty. Each area is dynamic, and interrelated with others with implications for overall MoH capacity for Telehealth. Given the findings of this thesis, the key influential determinants were identified for an improved Telehealth policy processes and provided invaluable information that will benefit real-world implementation of Telehealth at the national scale.